2007
DOI: 10.1007/bf03350807
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone stimulates adipogenesis and decreases osteoblastogenesis in human mesenchymal stem cells

Abstract: Thiazolidinediones (TZD) are widely prescribed for the treatment of Type 2 diabetes. Increased loss of bone mass and a higher incidence of fractures have been associated with the use of this class of drugs in post-menopausal women. In vitro studies performed in rodent cell models indicated that rosiglitazone (RGZ), one of the TZD, inhibited osteoblastogenesis and induced adipogenesis in bone marrow progenitor cells. The objective of the present study was to determine for the first time the RGZ-dependent shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 13 publications
3
67
0
Order By: Relevance
“…Although the mechanism by which TZDs act on bone is complex and not yet fully understood, these agents appear to have a direct effect on the differentiation of both osteoblasts and osteoclasts [11,45]. PPAR-γ has been shown in preclinical studies to promote the differentiation of mesenchymal stem cells into adipocytes rather than osteoblasts [46], and to promote osteoclast differentiation and increase osteoclast numbers [45]. In addition, exposure to TZDs appears to induce osteoblast and osteocyte apoptosis [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism by which TZDs act on bone is complex and not yet fully understood, these agents appear to have a direct effect on the differentiation of both osteoblasts and osteoclasts [11,45]. PPAR-γ has been shown in preclinical studies to promote the differentiation of mesenchymal stem cells into adipocytes rather than osteoblasts [46], and to promote osteoclast differentiation and increase osteoclast numbers [45]. In addition, exposure to TZDs appears to induce osteoblast and osteocyte apoptosis [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Through the promotion of PPARg, a common side effect of this class of drugs is weight gain, with increased adipogenesis leading to increased fat depots primarily within the subcutaneous site, along with the bone marrow. [123][124][125][126][127] The stimulation of differentiation has been widely associated with the increased adiposity in bone marrow seen during TZD treatment, though the reported effects of TZDs on osteoblasts and osteoclasts have been contradictory. Some reports have shown that exposure of multipotent cells to TZDs in vitro results in potent activation of adipogenesis, with no negative effects on osteoblast development or function, suggesting that the two cell types do not compete for the same population of precursor cells.…”
Section: Diabetic Medicationsmentioning
confidence: 99%
“…130 Yet, others have reported that induction of adipogenesis through PPARg stimulation does, in fact, necessarily reduce osteoblast differentiation and function, supporting the notion of a shared pool of progenitor cells. 123,[131][132][133] A number of prospective and retrospective observational investigations have aimed to determine whether TZD use is associated with a negative effect on bone density in humans. While two small studies reported a minor protective effect of troglitazone in reducing bone turnover, larger-scale surveys tend to purport a significant decrease in bone mass with TZD treatment.…”
Section: Diabetic Medicationsmentioning
confidence: 99%
“…This, in turn, will prevent the transition of the stem cells to osteoblasts while favouring adipogenesis. Previous studies have indeed shown that TZDs promote stem cell differentiation to adipocytes [5,6], although the mechanism(s) for this has so far been unknown. Although we only tested one TZD in the in vivo study we saw the induction of DKK1 in vitro with both rosiglitazone and pioglitazone, making it likely that this effect is intrinsic to PPARγ activation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) for this is not clear but several studies have shown that TZDs promote the differentiation of mesenchymal stem cells towards the adipose lineage rather than into osteoblastogenesis [5,6]. This, in turn, leads to fewer osteoblasts being available for differentiation, while adipose cell formation, including in the bone marrow, would be favoured.…”
Section: Introductionmentioning
confidence: 99%